Supplementation of antioxidant BHT to different bull semen extenders enhances semen quality after chilling - Mada, Khumran Armiya'u; Degu, Nurhusien Yimer; Yusoff, Rosnina; Omar, Mohamed Ariff; Haron, Abd Wahid; Kaka, Asmatullah; Ebrahimi, Mahdi; Aliyu, Abdulrasheed Bello (Universiti Putra Malaysia Press, 2017)
The effects of adding various concentrations of antioxidant, butylated hydroxytoluene (BHT) on chilled bull semen for 72 h at 4°C in Bioxcell® (BX), Tris egg-yolk- (TEY) and citrate egg-yolk- (CEY) based semen extenders were studied. Twenty-two ejaculates collected from three bulls, each extended using three extenders with BHT at 0 (control), 0.5, 1.0, 1.5, 2.0 and 3.0 mM/mL, were evaluated for sperm quality parameters. Extended semen was packaged into 0.25 mL straws containing 20 x 106 spermatozoa and chilled for 72 h. Four random straws each from the control and treatment groups were warmed at 37°C, pooled and evaluated using a computer-assisted semen analyser (IVOS Hamilton Thorne Biosciences) for general and progressive motilities, and for morphology, viability and acrosome damage using eosin-nigrosin stain under phase-contrast microscope. Results showed that sperm morphology, viability and protection of acrosome damage were significantly improved (p<0.05) at BHT concentrations of 0.5 in BX and 1.0 mM/mL in TEY and CEY compared to the controls. The BHT also showed a potential positive effect on progressive motility at 0.5 mM/mL in BX and 1.0 mM/mL in TEY and CEY. High concentrations of BHT (2.0 and 3.0 mM/mL), however, produced deteriorative effects on the sperm parameters in all the extenders. In conclusion, BHT when added at 0.5 mM/mL in BX and 1.0 mM/mL concentration to TEY and CEY extenders improved the quality parameters of bull chilled semen.